Associations of depressive symptoms and chronic diseases with activities of daily living among middle-aged and older population in China: A population-based cohort study - Hu, Yingyun; Zhou, Feixiang; Kaminga, Atipatsa Chiwanda; Yan, Shipeng; Hu, Zhao (Frontiers in Psychiatry, 2022)
Background: Activities of daily living (ADL) disability is a concern in the aging population and can lead to increased health service demands and lower quality of life. The aim of this longitudinal study was to assess the associations of chronic conditions and depressive symptoms with ADL disability. Methods: This prospective cohort study used two waves of data (2011 and 2015) from the China Health and Retirement Longitudinal Study (CHARLS). A total of 10,864 participants aged 45 and older were included for analysis. Chronic diseases were assessed by self-report and depressive symptoms were assessed using the validated 10-item of Center for Epidemiologic Studies Depression Scale at baseline. Incidents of ADL disability during follow-up were assessed using. the Katz ADL scales. Results: After 4 years of follow-up, there were 704 participants incidents of ADL disability. The incident rate was 17.22 per 1000 person-years. Having at least one chronic disease was independently associated with a 39% increased risk of incident ADL disability (adjusted HR, 1.39; 95%CI: 1.16, 1.67). The presence of depression symptoms was independently associated with a 54% increased risk of incident ADL disability (adjusted HR, 1.50; 95%CI: 1.30, 1.82). However, there was no significant additive interaction effect between chronic diseases and depressive symptoms on ADL disability. Conclusions: Chronic diseases and depressive symptoms are associated with an increased risk of ADL disability in middle-aged and older Chinese adults. Improving chronic diseases and depressive symptoms can prevent ADL disability.